2017
DOI: 10.1002/admi.201601064
|View full text |Cite
|
Sign up to set email alerts
|

Fused Nanojunctions of Electron‐Depleted ZnO Nanoparticles for Extraordinary Performance in Ultraviolet Detection

Abstract: Zinc oxide nanoparticles (ZnO-NPs) with radius of the Debye length have the optimal electron depletion effect for high-performance optoelectronic devices. However, a major challenge remains in assembling ZnO-NPs into three-dimensional (3D) interlinked networks for high-efficiency electron transport. Here an ultrafast thermal annealing (UTA) process has been developed by exposing the ZnO-NPs to excessive heat for a short period of 2 s. This enables the formation of NP-NP interface nanojunctions, resulting in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 41 publications
3
48
0
Order By: Relevance
“…In addition, photoluminescence (PL) was measured at room temperature on the ZnO‐NPs before and after the optimized plasma treatment for 30 min and the results are depicted in Figure S2. Both samples only exhibit a strong UV emission at ∼385 nm, which is usually considered as the characteristic band‐edge emission of crystalline ZnO . No apparent visible emission that is associated to the defects in crystalline ZnO was detectable in both samples.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, photoluminescence (PL) was measured at room temperature on the ZnO‐NPs before and after the optimized plasma treatment for 30 min and the results are depicted in Figure S2. Both samples only exhibit a strong UV emission at ∼385 nm, which is usually considered as the characteristic band‐edge emission of crystalline ZnO . No apparent visible emission that is associated to the defects in crystalline ZnO was detectable in both samples.…”
Section: Resultsmentioning
confidence: 97%
“…Among different nanostructures, ZnO nanoparticles (ZnO‐NPs) with uniform particle radius close to the Debye length (∼19 nm) have the most favorable morphology to take full advantage of the electron depletion effect, which is the key to high detection performance such as photoresponsivity ( R ), I Ph / I Dark , and detectivity ( D *) of the ZnO‐NP photodetectors, orders of magnitudes higher than that on their bulk counterparts . However, the fabrication of high‐crystallinity ZnO‐NPs is typically time‐consuming through a sequence of processes including synthesis, separation and dispersion of ZnO‐NPs and subsequent assembly of a thin film on target substrates with prepatterned electrodes followed by a thermal posttreatment, making it unattractive for large‐scale production .…”
Section: Introductionmentioning
confidence: 99%
“…We estimated the time constants of rise stage are t 1 ¼ 6.27 s and t 2 ¼ 37.1 s, and their relative weight factors are 85 and 15%, respectively, which give an average rise time constant of t r ¼ 11.02 s; the estimated time constants of the decay stage are t 1 ¼ 0.28 s and t 2 ¼ 6.85 s, with relative weight of 67 and 33%, respectively, producing an average decay time constant t d of 2.43 s. It was found that the rise process of NW array PD (1.38 s) is much faster than that of single NW PD (11.02 s), while the resetting process of ZnO NW array PD (4.05 s) is also comparable with that of single NW device (2.43 s). [6,9,11,14,16,19,20,22,25,27,[33][34][35][36][37][38][39][40][41][42] Compared to low temperature synthesized ZnO nanorods reported in reference, [35,36] ZnO NW arrays grown by CVD at high temperature have better crystal quality, which contributes to the high performance of our devices. Table 1 compares the photoresponse of different ZnO NW-based UV PDs as reported previously.…”
Section: Photoresponse Behavior Of Zno Nw Uv Pdsmentioning
confidence: 99%
“…Table 1 compares the photoresponse of different ZnO NW-based UV PDs as reported previously. [6,9,11,14,16,19,20,22,25,27,[33][34][35][36][37][38][39][40][41][42] Compared to low temperature synthesized ZnO nanorods reported in reference, [35,36] ZnO NW arrays grown by CVD at high temperature have better crystal quality, which contributes to the high performance of our devices.…”
Section: Photoresponse Behavior Of Zno Nw Uv Pdsmentioning
confidence: 99%
“…Semiconductor UV photodetectors (UVPDs) can be categorized into two types: photoconductive and photovoltaic. The photoconductive UVPDs cannot operate without extra power sources, which is applied to urge the photogenerated carriers to generate a photocurrent [2][3][4][5][6]. This largely enlarges the device size and weight, which leads to the disadvantages of miniaturization, wireless applications, and intellectualization.…”
Section: Introductionmentioning
confidence: 99%